1992
DOI: 10.1002/lsm.1900120111
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet laser‐induced fluorescence of colonic tissue: Basic biology and diagnostic potential

Abstract: Laser-induced fluorescence (LIF) of colonic tissue was examined both in vitro and in vivo to assess the ability of the technique to distinguish neoplastic from hyperplastic and normal tissue and to relate the LIF spectra to specific constituents of the colon. Spectra from 86 normal colonic sites, 35 hyperplastic polyps, 49 adenomatous polyps, and 7 adenocarcinomas were recorded both in vivo and in vitro. With 337-nm excitation, the fluorescence spectra all had peaks at 390 and 460 nm, believed to arise from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
233
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(245 citation statements)
references
References 27 publications
(15 reference statements)
12
233
0
Order By: Relevance
“…Many cell surface proteins, enzymes, hormones, etc., are also produced in larger amounts under disease conditions. 33 On the other hand, it is found that collagen fluorescence in oral tissue is reduced in malignancy, [36][37][38] which is attributed to both collagen lysis as well as thickening of the epithelial layer. It may therefore be thought that the Raman spectrum of normal tissue, which is basically mainly a lipid spectrum, should show changes that could be assigned to the additional molecular species mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…Many cell surface proteins, enzymes, hormones, etc., are also produced in larger amounts under disease conditions. 33 On the other hand, it is found that collagen fluorescence in oral tissue is reduced in malignancy, [36][37][38] which is attributed to both collagen lysis as well as thickening of the epithelial layer. It may therefore be thought that the Raman spectrum of normal tissue, which is basically mainly a lipid spectrum, should show changes that could be assigned to the additional molecular species mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…The possible contributions to the optical signal from metabolic cofactors NADH and FAD, collagen cross-links, and hemoglobin might be affected when tissue is resected, and the optimal activation wavelengths in vivo might differ from those determined on excised tissue. Schomaker et al 30 have demonstrated that NADH present in the tissue is oxidized to NAD + in anaerobic conditions initiated by tissue excision, and fluorescence from this metabolic cofactor decreases exponentially within 2 hours after the resection. To minimize this effect, we imaged the tissue immediately after excision, with the maximum time elapsed not exceeding 1 hour, minimally affecting tissue viability.…”
Section: Tumor Locationmentioning
confidence: 99%
“…Autofluorescence has been used to distinguish adenomatous polyps and normal colon 8 . Other sites for autofluorescence detection are, for example, the urinary bladder and the bronchus 9,10 .…”
Section: Introductionmentioning
confidence: 99%